2022
DOI: 10.3389/fimmu.2022.884248
|View full text |Cite
|
Sign up to set email alerts
|

Role of ADAM10 and ADAM17 in the Regulation of Keratinocyte Adhesion in Pemphigus Vulgaris

Abstract: The severe autoimmune blistering disease Pemphigus vulgaris (PV) is mainly caused by autoantibodies (IgG) against desmoglein (Dsg) 3 and Dsg1. The mechanisms leading to the development of blisters are not fully understood, but intracellular signaling seems to play an important role. Sheddases ADAM10 and ADAM17 are involved in the turnover of the desmosomal cadherin Dsg2 and ADAM10 has been shown to contribute to acantholysis in a murine pemphigus model. In the present study, we further examined the role of ADA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Nevertheless, EGFR signaling was not affected by TAPI-1 treatment, suggesting that EGFR might not be involved in ADAM17 inhibition-mediated positive adhesiotropy. A recent study in keratinocytes also revealed that ADAM17 inhibition did not alter EGFR signaling ( Kugelmann et al, 2022 ). In mice lacking DSG2, ADAM17 was increased in 2 week old hearts ( Ng et al, 2021 ).…”
Section: Discussionmentioning
confidence: 96%
“…Nevertheless, EGFR signaling was not affected by TAPI-1 treatment, suggesting that EGFR might not be involved in ADAM17 inhibition-mediated positive adhesiotropy. A recent study in keratinocytes also revealed that ADAM17 inhibition did not alter EGFR signaling ( Kugelmann et al, 2022 ). In mice lacking DSG2, ADAM17 was increased in 2 week old hearts ( Ng et al, 2021 ).…”
Section: Discussionmentioning
confidence: 96%
“…In cell‐based assays, the inhibition of ADAM10 exerts protective effects by preventing the autoantibody‐induced loss of intercellular adhesion in human keratinocytes. These results were limited to certain autoantibody profiles (antibodies against Dsg1 and Dsg3, but not Dsc3) and do not seem to hold true for every subtype of the disease [110]. ADAM10 is also involved in the direct regulation of Dsg2 turnover since it cleaves the desmosomal protein [111] (Fig.…”
Section: An Increasing Awareness Of Adam10's Role In Immune Regulatio...mentioning
confidence: 99%
“…Altogether, high Dsg3 and low Dsg1 autoantibody levels constitute a constellation where an inhibition of ADAM10 might be a favorable intervention to decelerate PV progression, even though there is still a lack of in vivo or even clinical data. Other autoantibody profiles have presented themselves as nonresponsive to ADAM10 inhibition [110].…”
Section: An Increasing Awareness Of Adam10's Role In Immune Regulatio...mentioning
confidence: 99%
“…224,225 Interestingly, signaling traits regulating cell adhesion are shared in different desmosome-related diseases. 14 Since signaling by p38MAPK and EGFR have been found to be upregulated in models of both pemphigus and arrhythmogenic cardiomyopathy and ADAM17 was found to regulate desmosomal adhesion in keratinocytes in pemphigus and also in cardiomyocytes, 214,[242][243][244] it is possible that cAMP signaling may also serve as a possible target in other desmosome-related diseases. In addition, cAMP signaling may be employed to regulate the behavior of other cells.…”
Section: Stabilize Cell Adhesion In Diseasementioning
confidence: 99%